Role of flux on synthesis of poly single crystals of Ce3+ doped yttrium aluminum garnet. Issue 3 (1st March 2016) - Song, Zhen; Zu, Rui; Liu, Xiaolang; He, Lizhu; Liu, Q.L.
Abstract : Yttrium aluminum garnet powders of good morphology are composed of tiny single crystals of regular faces. It is found that those tiny crystals grow from large clusters. The pomegranate‐like growth mechanism is driven by flux, which provides a semi‐liquid environment around the crystals. Abstract : Yttrium aluminum garnet powders of good morphology are composed of tiny single crystals of regular faces. However, the growth mechanism of those ploy single crystals remains unknown. This paper provides morphology images of particles uncrushed, and it is found that those tiny crystals grow from large clusters in a pomegranate‐like manner. The morphology change occurs after phase transition, and is driven by flux, which provides a semi‐liquid environment around the crystals. This paper is beneficial for understanding growth mechanism of poly tiny single crystals of yttrium aluminum garnet powders.